Respuesta :
Answer:
a) 16
b) 9
c) 16p +28q -r
Step-by-step explanation:
a) The desired coefficients are double those given, so we can multiply the given equation by 2 to get ...
2(4p +6q) = 2(8)
8p +12q = 16 . . . . the desired value
__
b) The desired coefficients are 1/5 of those given, so we can divide the given equation by 5 to get ...
(20q -5r)/5 = 45/5
4q -r = 9 . . . . the desired value
__
c) There are an infinite number of ways the values 16 and 9 can be combined to get 41. One of the simplest is ...
2×16 + 9 = 41
Substituting the expressions of part (a) and (b), we get ...
2×(8p +12q) +(4q -r) = 41
16p +28q -r = 41
Answer:
Step-by-step explanation:
4p + 6q = 8 ....multiply by 2
8p + 12q = 16 <==
========================
20q - 5r = 45 ....divide by 5
4q - r = 9 <===
========================
not sure I understand this one....
can it be something as simple as :
(8p + 12q) + (4q - r) + 16 ....because this equals 41
16 + 9 + 16